Qualidade de carne de bovinos suplementados com levedura viva e ureia protegida - Dombroski, Tiago (2015)
This study aimed to evaluate the quality of beef cattle finished grazing regime getting protein-energy supplementation with addition of urea protected and live yeast during the period of transition waters dry. To evaluate the carcass characteristics were used 75 Nellore bulls, with average weight and age of 27 months and 465.24 ± 2.16 kg, structured in a completely randomized design with 5 treatments and 15 repetitions. The treatments were: mineral supplement (SM), protein-energy (PE), PE with live yeast (PEL), PE with protected urea (PEU) and PE with yeast and protected urea (PELU). In quantitative and qualitative parameters sirloin samples were selected (musculus longissimus thoracis) of 8 animals per treatment randomized, organized by analysis of variance. For comparison of means was used decomposition of the sum of squares related to this source through orthogonal contrasts. The PE supplementation increased body weight compared to mineral supplementation. There was influence (P <0.05) in absolute values of the primal cuts in the carcasses of animals subjected to mineral supplementation; front, tipped needle and rear, obtained 100.93 ± 1.58; 23.16 ± 0.47; 121.79 ± 1.33 kg, respectively, compared to the average of other treatments, it was observed 104.49 ± 1.61 kg for front, 24.28 ± 0.47 kg for needle tip and 125.54 ± 1.31 kg for rear. However when the primary cuts were expressed in proportion to the cold carcass weight, no differences were detected (P> 0.05). Nutritional plans imposed on animals during the rainy season, regardless of the addition of yeast and / or protected urea, increase the body weight and carcass of such animals compared to mineral supplementation, without changing the composition and meat quality.